Efektifitas Proses Rekruitment SDM Perawat Bedah Di Rumah Sakit Umum Pekerja . - Riadi, Eka; Wiyono, Witji; Suryati, Adelina (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2024)
In the recruitment process in the operating room, it is necessary to quickly attract human resources, so the author conducted research on "Effectiveness of the HR Recruitment Process for Surgical Nurses in General Hospital Workers" due to the urgent need for HR Recruitment, Type and Research Approach. This type of research is a qualitative descriptive survey. and quantitative (type of research by observing, recording and documenting observations of population data only once at a time.),